PENGARUH ORIENTATION MARKET DAN PRODUCT INNOVATION TERHADAP PERFORMANCE MARKETING PADA PERUSAHAAN PT. NOVAPHARIN GRESIK - Shinta Dewi (Universitas 17 Agustus 1945 Surabaya, 2019)
This aims of this study is to determine the effect of orientation marketing andproduct innovation on performance marketing in PT. Novapharin Gresik. This type ofresearch is survey research and this study uses a quantitative approach. Sampling is doneby using a purposive sampling method that is with certain considerations so that thenumber of samples obtained is 100 people. Data was collected using a questionnaire thathad been tested for validity and reliability and carried out classical assumption tests. Thedata analysis technique used is multiple linear regression. This analysis model is used todetermine the effect of independent variables on the dependent variable. Empirically Theresults of the study show that there is a simultaneous influence of the OrientationMarketing and Product Innovation variables on Performance Marketing and partiallyinfluence, that Orientation Marketing has a positive and significant effect on PerformanceMarketing and Product Innovation has a positive and significant effect on PerformanceMarketing.Keywords: Orientation Marketing, Product Innovation, and Marketing Performance